Bacteroides fragilis outer membrane vesicles preferentially activate innate immune receptors compared to their parent bacteria - Gilmore, William J.; Johnston, Ella L.; Bitto, Natalie J.; Zavan, Lauren; O'Brien-Simpson, Neil; Hill, Andrew F.; Kaparakis-Liaskos, Maria (Frontiers in Immunology, 2022)
The ubiquitous release of bacterial membrane vesicles (BMVs) has become recognised as a key mechanism used by both pathogenic and commensal bacteria to activate innate immune responses in the host and mediate immunity. Outer membrane vesicles (OMVs) produced by Gram-negative bacteria can harbour various immunogenic cargo that includes proteins, nucleic acids and peptidoglycan, and the composition of OMVs strongly influences their ability to activate host innate immune receptors. Although various Gram negative pathogens can produce OMVs that are enriched in immunogenic cargo compared to their parent bacteria, the ability of OMVs produced by commensal organisms to preferentially modify their OMV contents and therefore enhance their immunostimulatory ability is less clear. In this study, we investigated the cargo associated with OMVs produced by the intestinal commensal Bacteroides fragilis and determined their ability to activate host innate immune receptors. Analysis of B. fragilis OMVs revealed that they packaged various biological cargo such as DNA, RNA, proteins, lipopolysaccharides (LPS) and peptidoglycan, and that this cargo could be enriched in OMVs compared to their parent bacteria. We visualised the entry of B. fragilis OMVs into intestinal epithelial cells, in addition to the ability of B. fragilis OMVs to transport bacterial RNA and peptidoglycan cargo into Caco 2 epithelial cells. Using HEK Blue reporter cell lines, we identified that B. fragilis OMVs could activate host Toll like receptors (TLR) 2, TLR4, TLR7 and nucleotide binding oligomerization domain containing protein 1 (NOD1), whereas B. fragilis bacteria could only induce the activation of TLR2. Overall, our data demonstrates that B. fragilis OMVs activate a broader range of host innate immune receptors compared to their parent bacteria due to their enrichment of biological cargo and their ability to transport this cargo directly into host epithelial cells. These findings indicate that the secretion of OMVs by B. fragilis may facilitate immune crosstalk with host epithelial cells at the gastrointestinal surface and suggests that commensal bacteria may modify their OMV content to preferentially activate host innate immune receptors at the mucosal gastrointestinal tract.